2006
DOI: 10.1007/s00520-006-0074-1
|View full text |Cite
|
Sign up to set email alerts
|

Supportive care needs of people with brain tumours and their carers

Abstract: Five recommendations to improve service delivery include: assignment of a dedicated member of the care team or case manager; proactive dissemination of information, education and psychosocial support; access to objective assessment of neuropsychological functioning; facilitating easier access to welfare payments; and services facilitating communication about difficult illness-related topics. Provision of services along these recommendations could improve supportive care of brain tumour patients and their carer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
150
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(160 citation statements)
references
References 35 publications
(36 reference statements)
8
150
0
1
Order By: Relevance
“…FCs report that they feel inadequate when they fail to meet the high standards they set for themselves. Those Information was one of the most important support needs for FCs of cancer patients [60][61][62][63][64][65]. FCs felt they were responsible for gathering information about the disease [61], and described becoming researchers, emphasizing the benefits of and necessity for being informed caregivers [66].…”
Section: Social Problems and The Need For Informationmentioning
confidence: 99%
“…FCs report that they feel inadequate when they fail to meet the high standards they set for themselves. Those Information was one of the most important support needs for FCs of cancer patients [60][61][62][63][64][65]. FCs felt they were responsible for gathering information about the disease [61], and described becoming researchers, emphasizing the benefits of and necessity for being informed caregivers [66].…”
Section: Social Problems and The Need For Informationmentioning
confidence: 99%
“…-Alistair, husband of Harriet (64-year-old woman with glioblastoma multiforme), interview after treatment (time 3) Most patients had a period of stability before their tumours gradually progressed, leading to more debilitating physical symptoms and cognitive decline. The burden of both the disease and its treatment were evident: Sometimes I get a bit tired … I think, the first few [treatments] I didn't really feel it.…”
Section: Dynamic Physical Trajectorymentioning
confidence: 99%
“…In previous research, patients and caregivers have reported anxiety and distress resulting from social isolation, stigmatization, feeling misunderstood and an inability to talk about their feelings or situation. 3,14,15 Both professional and informal social support are central to adapting to illness. 3,16 Patients with glioma have reported lower social support as their disease progressed and their functional abilities deteriorated.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that there are high levels of unmet needs among cancer patients; the most prominent relating to the provision of information and psychological support (Gustafson et al, 1993;Foot and Sanson-Fisher, 1995;Meredith et al, 1996;Sanson-Fisher et al, 2000;Janda et al, 2006;Barg et al, 2007). Although such research provides an indication on how to increase quality of care to cancer patients, there has been little quantitative research regarding the specific needs of patients with advanced, incurable cancer, creating uncertainty as to what areas need to be addressed when caring for this vulnerable population group.…”
mentioning
confidence: 99%